2022
DOI: 10.36873/jht.v17i2.5220
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strip Arrangement on Physical and Mechanical Properties Petung Bamboo Laminated Board (Dendrocalamus asper Backer)

Abstract: Penelitian ini bertujuan untuk mengetahui nilai sifat fisika dan mekanika papan laminasi bambu petung berdasarkan susuanan bilah kearah tebal dan pengaruh berat labur terhadap sifat fisika dan  mekanikanya.  Metode yang digunakan menggunakan metode eksperimen dengan rancangan percobaan menggunakan Rancangan Acak Lengkap (RAL) non faktorial dengan dua perlakuan berat labur serta tiga kali ulangan.  Berdasarkan hasil penelitian maka dapat ditarik beberapa kesimpulan mengenai sifat fisika dan mekanika papan lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
1
2
3
Order By: Relevance
“…As a whole, it is shown in Figure 5, the MOE values obtained follow the JAS 234:2003 standard with a minimum value of 75.000 kg/cm 2 . The value of MOE of laminated boards in this study was higher when compared to the zephyr-shaped laminated bamboo study of 80.000 kg/cm 2 [30] and in betung bamboo laminated boards of 10.001.77 kg/cm 2 [24]. From the results obtained, the MOE value of untreated bamboo was higher than treated bamboo.…”
Section: Modulus Of Elasticitycontrasting
confidence: 44%
See 1 more Smart Citation
“…As a whole, it is shown in Figure 5, the MOE values obtained follow the JAS 234:2003 standard with a minimum value of 75.000 kg/cm 2 . The value of MOE of laminated boards in this study was higher when compared to the zephyr-shaped laminated bamboo study of 80.000 kg/cm 2 [30] and in betung bamboo laminated boards of 10.001.77 kg/cm 2 [24]. From the results obtained, the MOE value of untreated bamboo was higher than treated bamboo.…”
Section: Modulus Of Elasticitycontrasting
confidence: 44%
“…Wahyudi [23] reported differences in density caused by differences in the number of layers of lamina. In addition, the density of bamboo varies based on the bamboo section and the conditions of the growing location [24]. Based on the results of the density analysis of variance, it was shown that immersion time had a significant effect on density.…”
Section: Densitymentioning
confidence: 99%
“…Nilai kerapatan papan laminasi kombinasi kayu rajumas dan bambu petung telah memenuhi standar SNI 01-6240-2000 yaitu sebesar 0,40-0,80 g/cm 3 . Penelitian ini bila dibandingkan dengan penelitian yang dilakukan oleh Wulandari & Amin (2023) pada papan laminasi kombinasi kayu sengon dan bambu petung dengan kisaran 0,45 -0,50 gram/cm³ maka termasuk lebih tinggi. Ikatan perekat pada kayu akan mengalami peningkatan seiring semakin meningkatnya kerapatan kayu dengan kisaran 0,7-0,8 gr/cm 3 dengan kadar air 12% (Mochsin et al, 2014).…”
Section: Berat Laburunclassified
“…Nilai MoR tersebut telah memenuhi standar JAS 234-2007 yaitu minimal 300 kgf/cm². Penelitian ini bila dibandingkan dengan penelitian yang dilakukan oleh Wulandari & Amin (2023) dengan nilai rata rata sebesar 329,25 kgf/cm 2 maka termasuk lebih rendah. Nilai MoR sangat erat kaitannya dengan kadar air dan kerapatan.…”
Section: Modulus Of Ruptureunclassified
See 1 more Smart Citation